System information system for data collection for community-based rehabilitation programs: Case study: Indonesian Center for Disability Studies and Information - Wawan Darmawan; Firdaus Nur (Jurnal Terapan Teknologi Informasi, 2022)
The Community Based Rehabilitation Program is a regional development program in terms of preventing disability/disability, detection and rehabilitation/habilitation of all aspects of life for the empowerment of persons with disabilities, families and communities. The design of this system uses information data collection methods by observation, literature study, and documentation. This research resulted in the RBM Program Data Collection Information System that can assist the organization of the Indonesian Center for Disability Studies and Information in managing the database, thus facilitating the process of evaluating and monitoring the Community-Based Rehabilitation program.